2023
DOI: 10.3390/microorganisms11061549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactiplantibacillus plantarum LPJZ-658 Supplementation on the Production, Meat Quality, Intestinal Morphology, and Cecal Microbiota of Broilers Chickens

Abstract: This study aimed to investigate the effects of L. plantarum LPJZ-658 on the production, meat quality, intestinal morphology, and cecal microbiota of broilers. White-feathered broilers (1 day old, n = 600) were randomly assigned to two groups and raised for six weeks. The individuals in the LPJZ-658 group were supplemented with 2.6 × 109 cfu/g LPJZ-658. The growth performance, meat quality, intestinal epithelium morphology, and cecal microbiota were observed. The results showed that the average daily gain, aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
(84 reference statements)
2
3
0
Order By: Relevance
“…In addition, we observed an increase in the abundance of Verrucomicrobiota in digesta following PSP supplementation, aligning with previous studies ( Liu et al, 2023a ; Liu et al, 2023b ). Liu et al (2023b) demonstrated that Verrucomicrobiota has the potential to enhance various intestinal aspects, such as VH and VH/CD ratio and the length of ileum and cecum. Another study by Liu et al (2023a) indicated the potential of Verrucomicrobiota in increasing intestinal villus height.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we observed an increase in the abundance of Verrucomicrobiota in digesta following PSP supplementation, aligning with previous studies ( Liu et al, 2023a ; Liu et al, 2023b ). Liu et al (2023b) demonstrated that Verrucomicrobiota has the potential to enhance various intestinal aspects, such as VH and VH/CD ratio and the length of ileum and cecum. Another study by Liu et al (2023a) indicated the potential of Verrucomicrobiota in increasing intestinal villus height.…”
Section: Discussionsupporting
confidence: 92%
“…LPJZ-658 is a strain of Lactiplantibacillus plantarum isolated by our group. Our practice has confirmed that LPJZ-658 improves lipid metabolism in late-laying laying hens and broiler chickens [39]. It is important to note that we found that LPJZ-658 ameliorated hepatic steatosis, inflammation, and fibrosis in NASH model mice by mediating bile acid metabolism and the gut microbiota [29], which suggests that LPJZ-658 has the potential to improve MASLD.…”
Section: Discussionsupporting
confidence: 76%
“…In recent years, growing evidence has established the therapeutic function of probiotics in the prevention/treatment of NAFLD [ 30 , 31 ]. In previous studies, we showed that LPJZ-658 supplementation improved the productivity of laying hens and broilers by modulating lipid metabolism and gut microbiota [ 27 ]. In the present study, we evaluated the impact of LPJZ-658 on NASH pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that LPJZ-658 contains a gene-encoding bile salt hydrolase (BSH), indicating that it may have the ability to regulate bile acid metabolism [ 26 ]. We further documented the effect of LPJZ-658 on improving the production performance and modulating the metabolism of both laying hens and broilers [ 27 ]. In the current study, we found that both LGG and LPJZ-658 were effective in the prevention of NASH, but LPJZ-658 was superior to LGG in liver injury and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%